Patent examination outcomes and the national treatment principle. (June 2014) - Webster, Elizabeth; Jensen, Paul H.; Palangkaraya, Alfons
<x xml:space="preserve">Abstract</x> One of the principles enshrined in all international patent treaties is that equal treatment should be provided to inventors regardless of their nationality. Little is known about whether this "national treatment" principle is upheld in practice. We analyze whether patent examination outcomes at the European and Japanese patent offices vary systematically by inventor nationality and technology area, using a matched sample of 47, 947 patent applications. We find that domestic inventors have a higher likelihood of obtaining a patent grant than foreign inventors and that the positive domestic inventor effect is stronger in areas of technological specialization in the domestic economy.